Epimaco Velasco NBI the true story (Viva Films, 1999)
A virtuous man dedicated to duty, Epimaco Velasco rose from the ranks to become one of the most admired directors of the National Bureau of Investigation. as an agent, he worked hard to solve many baffling cases, and as Bureau chief, he spearheaded the NBI in its quest to solve crimes and at the same time, to curb corruption among its ranks.